The Concept of Ta'dib According to An-Naquib Al-Attas And Humanism According to Paulo Freire and their Relevance with Islamic Education - Septoyadi, Zikry; Akbar, Akbar (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
A Naquib Al-Attas, with the idea of ta' dib, talks about to plan exercises to strengthen oneself in examining this open world. A Naquib Al- Attas is one of the figures who have impressive thoughts and figures in the improvement of contemporary Islamic training thought. Paulo Freire, with the concept of humanism, is interested in achieving the primary goal of education that humanizes humanity so that the potential within the subject of education can be developed. This study aims to describe and find essential points of thought of the concept of education, according to An-Naquib Al-Attas and Paulo Freire, and explain the relevance of the two figures' educational concepts with Islamic education. This research is qualitative. Furthermore, the type of research the writer chooses is library research with descriptive analysis. The primary data sources in this study are An-Naquib Al-Attas and Paulo Freire books that have been translated into Indonesian. Secondary data sources are taken from books relevant to the two educational concepts. Techniques of collecting data using techniques Implementing data that is analyzed with content. This exploration yielded results on the idea of ta' dib A Naquib Al-Attas and Paulo Freire's humanism that are applicable to Islamic instruction, while Freire's innovativeness despite everything bolsters the solid with common and training in Indonesia. No. 20 of 2003 can be affirmed.